Enhancing Vocabulary and Grammar Acquisition Through Instagram Quizzes: A Narrative Inquiry Approach - Setiyawan, Arisandi; Ummul Ma"rufa, Ika Meilinda; Hasanah, Yusrotul; Qulub, Khofifatul (English Education : English Journal for Teaching and Learning, 2025)
This study examines the effectiveness of Instagram quizzes as an interactive tool for enhancing vocabulary acquisition and grammar comprehension among English learners. This research employs a qualitative narrative inquiry approach, involving in-depth interviews and observational analysis of fifth-semester English language students at Universitas Islam Madura. Findings reveal that Instagram quizzes significantly enhance student engagement, motivation, and knowledge retention due to their interactive and gamified nature. A comparative analysis highlights the superiority of Instagram quizzes over traditional learning methods in terms of accessibility, immediacy of feedback, and sustained learner interest. However, challenges such as internet dependency, screen fatigue, and over-reliance on digital tools underscore the necessity for a balanced pedagogical approach.